KETAHANAN ORGANISASI MASYARAKAT (ORMAS) DALAM KERAGAMAN IDEOLOGI ISLAM PADA MASYARAKAT DI INDONESIA (STUDI KASUS PADA ORGANISASI WAHDAH ISLAMIYAH) - Andi Asyhary J. Arsyad; Hafied Cangara; Arianto Arianto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2020)
This study aims to understand the resilience of the Wahdah Islamiyah organization to the diversity of Islamic ideologies in Indonesian society. The research method uses a descriptive qualitative case study approach. The data is then extracted from two types of sources, primary and secondary, and then analyzed using the concept of Miles and Huberman data analysis. The result is that the organizational resilience achieved by Wahdah Islamiyah is part of creating an ecosystem between the organization and its surroundings. In the face of a multi-ideological society, Wahdah Islamiyah was well received due to his